Experiencing Stress among Nurses during Resuscitation Procedure and Legal Obligations for Healthcare Workers in Slovenia - Koželj, Anton; Strauss, Maja; Strnad, Matej (Medicine, Law & Society, 2020)
Nurses are always part of the team that performs resuscitation procedures. In this paper the authors explore the influence that resuscitation procedures on nurses who perform them. For data collection, the authors used a survey with a convenience sample of nurses who work in emergency settings. For statistical processing of data, the authors used the calculation of frequency, standard deviation, means, and median. Authors used Spearman's rank correlation coefficient and calculated the p-value. The respondents in the survey completed the Post-Code Stress Scale. The results show that the majority of the respondents experienced resuscitation cases as burdensome situations; however, the level of stress was moderate. Nurses still experience some physical and psychological symptoms during resuscitations.